PENGARUH PENDIDIKAN GIZI DENGAN MEDIA KARTU KUARTET TERHADAP KEBIASAAN SARAPAN, ASUPAN ENERGI DAN PROTEIN SARAPAN, DAN PENGETAHUAN GIZI TENTANG SARAPAN DI SDN PEDURUNGAN KIDUL 01 DAN 02 KOTA SEMARANG - Farida Rahmah; Astidio Noviardhi; Setyo Prihatin; Cahyo Hunandar; Ana Yuliah Rahmawati (JURNAL RISET GIZI, 2019)
Background : Health education with the methods in games is more interesting than counseling methods in the classroom.  The using of Quartet card media is the way as an alternative media to give information about the nutrition, which one using the game. Providing nutrition education through quartet card media is expected to increase breakfast habits, breakfast energy and protein intake and nutrition knowledge especially for elementary school.Objectives : To determine the effect of nutrition education on quartet card media on breakfast habits, breakfast energy and protein intake and nutritional knowledge about breakfast in elementary school students. Method : This study used the quasy experiment method with a pre test, post test and control group design. The Sampling was done by randomly to get 26 treatment samples and 26 control samples at the Elementary School in Pedurungan Kidul 01 and 02  Semarang City. The data collected were sample identity card (name, age, gender, parental education, parental work), breakfast habits, breakfast energy and protein intake and nutritional knowledge about breakfast. Data was collected by interview and answering the questionnaire. The results of bivariate analysis using the Paired T-Test, Wilxocon, Independent T-Test and Mann Whitney test.Results : There was an effect of increasing breakfast habits by an average of 1.71 ± 0.58, an increase in the amount of breakfast energy and protein intake and nutritional knowledge in the treatment group and a decrease in breakfast habits by an average of -0.34 ± 0.12 in control group before and after providing nutrition education through quartet card media with a value of p 0.05.Conclusion : Quartet card media about breakfast increases breakfast habits, breakfast energy and protein intake and nutritional knowledge in the treatment group.